Understanding Cyberbullying on social media for Youth in the Coastal Areas of Pematang Guntung Village - pahlevi hidayat, Fadhil Pahlevi Hidayat; ramadhan samosir, Wahyudi Ramadhan Samosir; aflarisa, Nindia Aflarisa (Universitas Ahmad Dahlan, 2022)
Many cases of cyberbullying happen to teenagers, but in Indonesia the empirical topic of cyberbullying has not been widely used, especially in rural adolescents in coastal areas, especially Pematang Guntung Village. This paper aims to analyze cases of cyberbullying in Pematang Gunung Village on social media. The method used in this research is qualitative. The research location in this study was carried out in the coastal area of ​​Pematang Guntung Village by determining which informants would be used to obtain data. The researcher used purposive sampling technique. The results showed that most of the teenagers in the coastal area of ​​Pematang Guntung Village knew about cyberbullying on social media. This is because the phenomenon of cyberbullying is not something new and they often encounter them on their social media accounts, especially on Facebook and Instagram. However, teenagers on the coast of Pematang Guntung Village still do not understand cyberbullying in the literature, starting from the definition of cyberbullying, the types of cyberbullying, and regulations regarding cyberbullying. This is because the phenomenon of cyberbullying is not new and they often encounter them on their social media accounts, especially on Facebook and Instagram.